2014
DOI: 10.1080/01614940.2014.953356
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrogen Catalysis: A Remarkable Avenue in the Reactivity of Molecular Hydrogen

Abstract: Molecular hydrogen is the simplest and most abundant compound in the universe and is involved in numerous industrial chemical processes. In conventional chemistry, dihydrogen typically plays the role of a reductant and a reagent for homogeneous and heterogeneous hydrogenation processes such as the industrial and enzymatic ammonia formation, reduction of metallic ores and hydrogenation of unsaturated fats and oils. However, there are also processes in which molecular hydrogen participates as promoter, and even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 140 publications
(274 reference statements)
0
31
0
Order By: Relevance
“…Since then, several new (typically small) molecular and ionic systems have been discovered to involve roaming dynamics. 69,[81][82][83][84]92,93 A novel molecular mechanism was proposed in our previous study 101 for the photochemical dissociation of formaldehyde assisted by the H 2 coproduct, which leads to the same product set of (CO + H 2 ). Based on our calculations, the dihydrogen catalysis has a relatively low barrier of activation (as low as 64.8 kcal/mol at M06-2X/cc-pVTZ level, compared to 79 kcal/mol for the uncatalyzed dissociation and 86.6 kcal/mol for the radical decomposition).…”
Section: Introductionmentioning
confidence: 97%
“…Since then, several new (typically small) molecular and ionic systems have been discovered to involve roaming dynamics. 69,[81][82][83][84]92,93 A novel molecular mechanism was proposed in our previous study 101 for the photochemical dissociation of formaldehyde assisted by the H 2 coproduct, which leads to the same product set of (CO + H 2 ). Based on our calculations, the dihydrogen catalysis has a relatively low barrier of activation (as low as 64.8 kcal/mol at M06-2X/cc-pVTZ level, compared to 79 kcal/mol for the uncatalyzed dissociation and 86.6 kcal/mol for the radical decomposition).…”
Section: Introductionmentioning
confidence: 97%
“…This is a surprising discovery. Hydrogen adsorption and activation is one of the most studied reactions in all of chemistry; early investigations into the interactions between hydrogen and various metals date back to the mid-19th century. Hydrogenation reactions over heterogeneous catalysts are widely used in industry and have been studied for over a century. Similarly, the mechanism of hydrogen activation by inorganic complexes, dating back to seminal work by Wilkinson and Vaska, has been widely studied for more than 50 years . The overwhelming majority of these studies show that hydrogen activation occurs via similar mechanisms: oxidative addition for transition metal complexes , and (homolytic) dissociative chemisorption for metals and supported metal catalysts. , …”
Section: Introductionmentioning
confidence: 99%
“…As a major precursor of atmospheric aerosols, H 2 SO 4 plays an important role in climate by affecting the characteristics of clouds. 23,24 It has been demonstrated 25−28 that H 2 SO 4 can exert a positive catalytic influence on atmospheric hydrolysis reaction routes 21,22,27−29 and hydrogen-transfer pro-cesses 25,26,28,30,31 by reducing the magnitude of the activation barrier 25−32 and promoting the effect of hydrogen transfer. 21,22 Compared with the catalysts H 2 O, NH 3 , and HCOOH, H 2 SO 4 may have better catalytic effects for some reaction systems.…”
Section: Introductionmentioning
confidence: 99%
“…As a major precursor of atmospheric aerosols, H 2 SO 4 plays an important role in climate by affecting the characteristics of clouds. , It has been demonstrated that H 2 SO 4 can exert a positive catalytic influence on atmospheric hydrolysis reaction routes ,, and hydrogen-transfer processes ,,,, by reducing the magnitude of the activation barrier and promoting the effect of hydrogen transfer. , Compared with the catalysts H 2 O, NH 3 , and HCOOH, H 2 SO 4 may have better catalytic effects for some reaction systems. ,,,,,, Consequently, it is worth inquiring about whether H 2 SO 4 has a catalytic effect in promoting the hydrolysis of CH 2 OO. Besides, previous investigations showed that the formation of H 2 SO 4 ···H 2 O or (H 2 SO 4 ) 2 is probably the first step in the process of nucleation when H 2 SO 4 is responsible for nucleation.…”
Section: Introductionmentioning
confidence: 99%